A pilot randomized sham controlled trial of bilateral iTBS for depression and executive function in older adults. (9th December 2022) - Cristancho, Pilar; Arora, Jyoti; Nishino, Tomoyuki; Berger, Jacinda; Carter, Alexandre; Blumberger, Daniel; Miller, Philip; Snyder, Abraham; Barch, Deanna; Lenze, Eric J.
Abstract: Introduction: Executive function deficits (EFD) in late life depression (LLD) are associated with poor outcomes. Dysfunction of the cognitive control network (CCN) has been posited in the pathophysiology of LLD with EFD. Methods: Seventeen older adults with depression and EFD were randomized to iTBS or sham for 6 weeks. Intervention was delivered bilaterally using a recognized connectivity target. Results: A total of 89% (17/19) participants completed all study procedures. No serious adverse events occurred. Pre to post‐intervention change in mean Montgomery‐Asberg‐depression scores was not different between iTBS or sham, p = 0.33. No significant group‐by‐time interaction for Montgomery‐Asberg Depression rating scale scores ( F 3, 44 = 0.51; p = 0.67) was found. No significant differences were seen in the effects of time between the two groups on executive measures: Flanker scores ( F 1, 14 = 0.02, p = 0.88), Dimensional‐change‐card‐sort scores F 1, 14 = 0.25, p = 0.63, and working memory scores ( F 1, 14 = 0.98, p = 0.34). The Group‐by‐time interaction effect for functional connectivity (FC) within the Fronto‐parietal‐network was not significant ( F 1, 14 = 0.36, p = 0.56). No significant difference in the effect‐of‐time between the two groups was found on FC within the Cingulo‐opercular‐network ( F 1, 14 = 0, p = 0.98). Conclusion: Bilateral iTBS is feasible in LLD. Preliminary results are unsupportive of efficacy on depression, executive function or target engagement of the CCN. A future Randomized clinical trial requires a larger sample size with stratification of cognitive and executive variables and refinement in the target engagement. Key points: ITBS over bilateral dorso‐lateral‐prefrontal‐cortex in older adults with depression and executive function deficits was feasible and without serious side effects. This pilot study was unsupportive of the efficacy of bilateral iTBS for treating depression or executive function deficits (visuospatial inhibitory attention, cognitive flexibility, working memory) in older adults. Preliminary evidence showed no changes on resting state functional connectivity within the fronto‐parietal‐network, cingulo‐opercular‐network and default‐mode‐network, which are posited in the pathophysiology of late life depression.